Strain Engineering of the Berry Curvature Dipole and Valley Magnetization in Monolayer MoS2 - Son, Joolee; Kim, Kyung Han; Ahn, Y. H.; Lee, Hyun Woo; Lee, Jieun (Physical Review Letters, 2019)
The Berry curvature dipole is a physical quantity that is expected to allow various quantum geometrical phenomena in a range of solid-state systems. Monolayer transition metal dichalcogenides provide an exceptional platform to modulate and investigate the Berry curvature dipole through strain. Here, we theoretically demonstrate and experimentally verify for monolayer MoS2 the generation of valley orbital magnetization as a response to an in-plane electric field due to the Berry curvature dipole. The measured valley orbital magnetization shows excellent agreement with the calculated Berry curvature dipole, which can be controlled by the magnitude and direction of strain. Our results show that the Berry curvature dipole acts as an effective magnetic field in current-carrying systems, providing a novel route to generate magnetization.
Keywords: In-plane electric fields; Novel route; Orbital magnetization; Physical quantities; Solid-state system; Strain engineering; Transition metal dichalcogenides